Fabrication and Characterization of Anti Corrosion Titnia-‎Nanocompsite Coatings for Biomedical Applications (Journal of University of Babylon for Engineering Sciences, 2024)
Titanium dioxide nanoparticles merged with chitosan biopolymer as coatings were deposited on 316L SS substrate via pulsed-cathodic electrophoretic deposition mode (PCEPD) technique with different duty cycle and deposition time to enhance implant surface and electrochemical performance of biomedical implant in ringer solution. A homogeneous distribution of the Titania nanoparticles in coatings with crack free were obtained for utilizing in medical field. Surface, morphological and structural characterization of the composite coatings were investigated by using Field Emission Scan Electron Microscope (FE-SEM), Fourier transform infrared spectroscopy (FT-IR) and X-RAY diffraction technique. The corrosion behavior of the coated substrate was evaluated using potentiodynamic polarization technique (PDP) in Ringer's solution at 37 ºC. The results showed that the chitosan-TiO2 coated 316L SS substrate exhibited better corrosion resistance compared to the uncoated one.